The efficacy of Clare’s Law in domestic violence law reform in England and Wales - Fitz-Gibbon, Kate (Criminology & criminal justice, 2017)
In 2011 the high profile murder of Clare Wood led to the introduction of the national domestic violence disclosure scheme (‘Clare’s Law’) in England and Wales. The scheme aims to prevent the perpetration of violence between intimate partners through the sharing of information about prior histories of violence. Despite already spreading to comparable jurisdictions in the UK and Australia, to date the merits of a domestic violence disclosure scheme have been the subject of limited scholarly review and analysis. This article provides a timely critical analysis of the need for and merits of Clare’s Law. It examines the data impediments to the scheme, the need to balance the right to protection with the right to privacy and the question of victim empowerment versus responsibilization and victim blaming. The article concludes that there is a need to heed caution in adopting this policy elsewhere.